Vitiligo-Like Lesions in a Patient with Metastatic Breast Cancer Treated with Cyclin-Dependent Kinase (CDK) 4/6 Inhibitor: A Case Report and Literature Review - Sharaf B; AlMasri R; Abdel-Razeq N; Salama O; Hamad I; Abunasser M; Abdel-Razeq H (Dove Medical Press, 2022)
Baha' Sharaf,1 Rama AlMasri,2 Nayef Abdel-Razeq,3 Osama Salama,1 Ibrahim Hamad,1 Mahmoud Abunasser,1 Hikmat Abdel-Razeq1,4 1Department of Internal Medicine, King Hussein Cancer Center, Amman, Jordan; 2Department of Internal Medicine, Istishari Hospital, Amman, Jordan; 3Department of Internal Medicine, Henry Ford Hospital, Detroit, MI, USA; 4School of Medicine, University of Jordan, Amman, JordanCorrespondence: Hikmat Abdel-RazeqDepartment of Internal Medicine, King Hussein Cancer Center, School of Medicine, University of Jordan, Queen Rania Al Abdullah Street, PO Box 1269, Amman 11941, JordanTel + 962-6 5300460, Ext: 1000Email habdelrazeq@khcc.joBackground: Cyclin-dependent kinase (CDK) 4/6 inhibitors have revolutionized the treatment landscape of hormone receptor-positive (HR+), human epidermal growth factor receptor 2-negative (HER2−) metastatic breast cancer, with an impressive efficacy and safety profile. Cytopenia is the main adverse event, which is both predictable and manageable. Here, we report a case of CDK4/6 inhibitor-induced vitiligo-like lesions. Vitiligo or vitiligo-like lesions are a rare adverse event; only a few cases are reported in the literature.Case Presentation: A 71-year-old female patient was diagnosed initially with early-stage right breast cancer (HR+/HER2−) and was treated with breast-conserving surgery followed by chemotherapy, radiotherapy, and hormonal therapy. A few years later, she developed metastatic disease to the hilar lymph nodes, and to multiple skeletal sites, including the left scapula, left shoulder, left iliac bone, and dorsal vertebrae, for which she was treated with ribociclib and letrozole. While on treatment, she developed hypopigmented lesions involving both hands, feet, and face, which were described as vitiligo-like lesions.Conclusion: CDK4/6 inhibitor-induced vitiligo is a rare and unpredictable adverse event. This case report highlights the rarity of this adverse event, the dilemma related to the optimal treatment, and decisions related to continuation, holding, or switching CDK4/6 inhibitors.Keywords: CDK4/6 inhibitors, ribociclib, vitiligo, vitiligo-like, breast cancer, skin adverse events